36. Potential interest of protons comparing SRT and IMRT with photons for cases where prescribed dose is limited by OAR constraints. (December 2016) - Wagner, A.; Lacornerie, T.; Cayez, R.; Mirabel, X.; Reynaert, N.
Abstract : Introduction: It is widely admitted that dose distributions obtained with protons are more conformal compared to photons. We investigate the role of protontherapy for those cases where it was not possible to fulfill OAR constraints with most advanced photon techniques and where the prescribed dose had to be decreased. This study investigates all cases where protontherapy provides a better OAR sparing compared to photons in general, but focuses only on the difficult cases as described above. Methods: During 2015, all SRT/SBRT cases with CyberKnife and helical Tomotherapy where prescribed dose to target volumes had to be decreased to fulfill OAR dose constraints were listed. They were replanned with an IBA proton machine using the Pencil Beam Scanning technique on a RaySearch workstation, with the same PTV as photons. Range uncertainties were not taken into account, except while selecting the beam incidences. Results: Among the 1310 SRT/SBRT and IMRT treatments, the plans that needed a decreased prescription dose can be classified in two categories: - When a serial organ is adjacent and limiting, as spinal cord for vertebra re-irradiation. - When a parallel organ received too much low doses when target volumes are too big, as for liver where 700 cm 3 must receive less than a threshold. For the first category, proton plans didn't allow delivering the initial prescribed dose either. The penumbra of Pencil Beam Scanning (3 mm spot) is not sharper compared to SRT/SBRT plans. For the second category, consisting of 11 liver lesions and 6 lung lesions with mediastinal nodes, initial prescribed dose can always be delivered when using the PBS technique. Conclusions: Over one year, we counted 17 patients where it was necessary to decrease prescribed dose when applying photon treatments and where protons plans showed that the prescribed dose can be delivered. This is especially the case for large volumes in lung or liver.